PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Syntha Noviyana; Mella Sri Kencanawati; Reni Anggraini; Muhammad Farhan Ramdhani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Financial distress is a condition when the company experiences financial difficulties and occurs before bankruptcy. This condition occurs when a company suffers losses for several years. This study aims to analyze the effect of profitability, liquidity, and leverage on financial distress partially and simultaneously in transportation subsector companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The population in this study is the transportation sub-sector listed on the Indonesia Stock Exchange, amounting to 46 companies. This research was conducted using purposive sampling method. Companies that meet the criteria to be used as samples in this study amounted to 7 companies. The type of data used is secondary data in the form of financial statements of transportation subsector companies listed on the Indonesia Stock Exchange for the 2018-2020 period obtained through the official website of the Indonesia Stock Exchange and the official website of each company. The analysis technique in this study uses multiple linear regression analysis with SPSS software version 25. The results of this study indicate that partially profitability as measured by Return on Assets (ROA) and liquidity as measured by Current Ratio (CR) has no effect on financial distress. Meanwhile, leverage as measured by the Debt to Assets Ratio (DAR) has an influence on the occurrence of financial distress in a company. Simultaneously profitability, liquidity, and leverage affect financial distress.